2022
DOI: 10.1007/s10482-022-01770-4
|View full text |Cite
|
Sign up to set email alerts
|

Sponge holobionts shift their prokaryotic communities and antimicrobial activity from shallow to lower mesophotic depths

Abstract: In this study, we used 16S rRNA gene amplicon sequencing to investigate prokaryotic community composition of the Caribbean sponges Xestospongia muta and Agelas sventres from three depth ranges: < 30 m (shallow), 30–60 m (upper mesophotic), and 60–90 m (lower mesophotic). The prokaryotic community in shallow samples of X. muta was enriched in Cyanobacteria, Chloroflexota, and Crenarchaeota compared to samples from mesophotic depths, while mesophotic samples of X. muta were enriched in Acidobacteriota. For A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 112 publications
(134 reference statements)
1
5
0
Order By: Relevance
“…These differences were mainly attributed to the relative abundance of the bacterial orders rather than their identity, which was similar at all depths (Figure 3A). These findings are in line with previous studies that compared microbial assemblages in relation to depth, and revealed similar patterns (Morrow et al, 2016;Indraningrat et al, 2022). Along the shallow to mesophotic depths the physical, biochemical, and biotic factors undergo change (Lesser et al, 2018).…”
Section: Mesophotic and Shallow Microbial Communities: General Descri...supporting
confidence: 92%
See 1 more Smart Citation
“…These differences were mainly attributed to the relative abundance of the bacterial orders rather than their identity, which was similar at all depths (Figure 3A). These findings are in line with previous studies that compared microbial assemblages in relation to depth, and revealed similar patterns (Morrow et al, 2016;Indraningrat et al, 2022). Along the shallow to mesophotic depths the physical, biochemical, and biotic factors undergo change (Lesser et al, 2018).…”
Section: Mesophotic and Shallow Microbial Communities: General Descri...supporting
confidence: 92%
“…Many bacterial members have been found to change in abundance between the wild-type shallow and mesophotic sponges. For example, ASV members of the order Caldilineales (Chloroflexi) were enriched in the wild-shallow samples, as found for the sponges X. muta and Agelas sventres (Indraningrat et al, 2022). In the mesophotic sponges, a higher abundance of Nitrospirota bacteria was found (Figure 3A).…”
Section: Mesophotic and Shallow Microbial Communities: General Descri...mentioning
confidence: 71%
“…In addition, the SVA0996 marine group has also been detected in the mucus, tissue, and skeleton of the reef coral Porites lutea (Kuang et al 2015), the Mediterranean coral, Astroides Fig. 8 Non-metric multidimensional scaling (nMDS) plots for the A Agulhas National Park (ANP) samples and the B Springfield Farm (Areas 1-3) samples, showing the actinobacterial community similarities and the key environmental drivers for these communities calycularis (Biagi et al 2020), found in association with marine sponges (Slaby et al 2017;Turon et al 2019;Verhoeven 2019;Indraningrat et al 2022), found in association with the brown alga, Laminaria digitata (Ihua et al 2020), the macro-alga, Taonia atomaria (Paix et al 2019), and ascidians (Tunicata) (Steinert et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the Sva0996 marine group in sponges is unknown, Orsi et al (2016) showed that this group is involved in dissolved protein cycling in the ocean, while Indraningrat et al (2022) reported that this taxon may be present where high nitrate concentrations are found, as well as in high productivity areas. A study by Biagi et al (2020) confirmed the potential of this marine group to utilise organic nitrogen, where it has been shown that stressed reef-building corals produce mucus with a higher protein content.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of sponge samples was conducted following a previously published protocol, with adjustments made to the quantity of starting materials (Tsukamoto et al, 2010;Rohde et al, 2015;Indraningrat et al, 2022).…”
Section: Sponge Extractionmentioning
confidence: 99%